RELATIONSHIP OF LIFE SKILLS EDUCATION WITH INTEREST IN LEARNING AND ENTREPRENEUR MOTIVATION OF EQUALITY PROGRAM STUDENTS IN PKBM, PAITON DISTRICT, PROBOLINGGO REGENCY - Endang Sri Wahyuni; I Ketut Atmaja; Soedjarwo Soedjarwo (Fakultas Ilmu Pendidikan-Universitas Negeri Malang, 2021)
Life skills education is thought to have a contribution to learning interest and entrepreneurial motivation in equivalence students. The concept of life skills education applied to equivalence students is based on the ability to be independent and able to solve problems. The concept is suspected to have an indirect effect on interest in learning and entrepreneurship. The purpose of the study was to prove the relationship between life skills and interest in learning and entrepreneurial motivation. The study used a descriptive correlational approach to data collection methods using a questionnaire. The data analysis technique uses the SPSS application with the Pearson correlation product moment test. 250 students of equivalence package C from PKBM Al Fatih and Nurul Falah were selected as research samples. The results of the Pearson correlation on life skills education with learning interest are 0.360 with a value of sig.(2-tailed) 0.000 <0.005. This means that there is a positive and significant relationship between life skills education and interest in learning. In the life skills education variable with entrepreneurial motivation, the Pearson correlation value is 0.585 with a sig. (2-tailed) 0.000 < 0.005. This means that there is a positive and significant relationship between life skills education and entrepreneurial motivation. The conclusion of this study is that there is a positive relationship between life skills education with learning interest and entrepreneurial motivation. Therefore, it is necessary to have a scheduled life skills education program for equivalence students.